Remote entryway smart lock system / Nur Suraya Mohd Zain … [et al.] - Mohd Zain, Nur Suraya; Suhaimi, Mohd Saiful Azri; Norazaki, Fakhrul Akif; Mat Soid, Nuraina Alia; Ahmad Zubir, Siti Hajar; Omar, Siti Nazirah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Basically, this product is made to tighten the security and safety of the house. Remote entryway smart lock system is a system that is more secure for our house in order to avoid any danger to the family and the belongings. The product will be installed at the door between inside and outside of the house and it can be assessed through smartphone. The system will alert the user if someone tries to enter the house or tries to break the door system. Thus, if the owner is not at the house and any suspicious entry occurs, the notification will automatically pop up on the phone and the owner will realize what happened to the house in just a minute. The most typical issues when using the apps are a lost Wi-Fi connection or a lost smartphone, and everything will be messed up. However, with our product, the users can still use the "thumbprint feature" as a backup. Remote Entryway Smart Lock System has a lot of potential and commercial value to be marketed both locally and globally if it gets the opportunity and exposure as it deserves, especially in this era of industrial revolution 4.0. This innovation product is created and made to conserve the human energy for more beneficial works and it’s also ideal for those who is aware of their safety at home with children or disable person. The unnecessary use of a physical key is a must for them as they are usually at risk of losing the key and unable to reach the door.